The effects of iron deficiency anemia on sleep and life qualities - Sincan, Gulden; Sincan, Suat; Bayrak, Muharrem (Annals of Medical Research, 2022)
Aim: Iron deficiency anemia is an important public health problem all over the world. We aimed to determine the effects of anemia on sleep and life qualities in patients with iron deficiency anemia. Material and Methods: Ninety-nine iron deficiency anemia patients and fourty healthy cases were recruited. Short-Form 36-Item Health Survey questionnaire and Pittsburgh Sleep Quality Index questionnaire were used to measure the qualities of life and sleep, respectively. A Pittsburgh Sleep Quality Index global score >5 was defined as poor sleep quality. The gathered data were analyzed using descriptive, independent-t-test, chi-square tests. Results: The global Pittsburgh Sleep Quality Index score was 10.23±2.87 in patients with iron deficiency anemia and it was 3.65±1.4 in control group (p
Keywords: Iron deficiency anemia; life quality; sleep quality